2018
DOI: 10.1101/gr.233874.117
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic maintenance of topological domains in the highly rearranged gibbon genome

Abstract: The relationship between evolutionary genome remodeling and the three-dimensional structure of the genome remain largely unexplored. Here, we use the heavily rearranged gibbon genome to examine how evolutionary chromosomal rearrangements impact genome-wide chromatin interactions, topologically associating domains (TADs), and their epigenetic landscape. We use high-resolution maps of gibbon-human breaks of synteny (BOS), apply Hi-C in gibbon, measure an array of epigenetic features, and perform cross-species co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
97
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 72 publications
19
97
1
Order By: Relevance
“…We obtained samples for homokaryotypic carriers of 2Rb, 2Rbc, and 2Rd arrangements (see Methods). For each colony or arrangement, we produced Hi-C libraries for pools of 5 whole adult mosquitos or 15-25 larvae following the library preparation protocol in (Lazar et al 2018) . We sequenced each library on a fraction of a Hiseq 4000 lane and obtained 12 million read pairs on average per sample.…”
Section: Stocks and Sequencing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained samples for homokaryotypic carriers of 2Rb, 2Rbc, and 2Rd arrangements (see Methods). For each colony or arrangement, we produced Hi-C libraries for pools of 5 whole adult mosquitos or 15-25 larvae following the library preparation protocol in (Lazar et al 2018) . We sequenced each library on a fraction of a Hiseq 4000 lane and obtained 12 million read pairs on average per sample.…”
Section: Stocks and Sequencing Resultsmentioning
confidence: 99%
“…We then filtered the homogenate through a 40um screen and fixed nuclei with 1% formaldehyde. We produce Hi-C libraries as described in (Lazar et al 2018) , and we sequenced each library on a portion of a Hiseq 4000 lane.…”
Section: Hi-c Library Preparation and Sequencingmentioning
confidence: 99%
“…Another study demonstrated that evolutionary changes in TAD structure correspond with the creation or elimination of CTCF binding sites using relatively low resolution Hi-C data from rhesus macaque, dog, rabbit, and mouse (Rudan et al, 2015). More recently, TADs have been shown to have strong conservation in mammalian evolution with the TADs boundaries under potential negative selections against genome rearrangements (Lazar et al, 2018;Fudenberg and Pollard, 2019). These previous analyses pointed to the conservation and changes of 3D genome structure across different species, although a more comprehensive characterization of the detailed evolutionary patterns of 3D genome organization remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…If TAD structure is critical for proper gene regulation, then the evolution of 3D genome organization should be highly constrained and related species should show strong conservation of TAD structures. Consistent with this prediction, a variety of studies in vertebrates have reported strong conservation of 3D genome organization using comparative Hi-C approaches [8,50,26,28] . A recent study in Drosophila reported that 3D genome architecture is conserved over 40 million years of evolution in spite of extensive chromosomal rearrangements [41].…”
Section: Introductionmentioning
confidence: 58%